"Man Looks at the Outward Appearance, God Looks at the Heart:" Inclusion and Identity in a High Boundary Religion. Issue 1 (31st March 2021) - Walker, Jonathan; Fitzgerald, Scott T.
Abstract : In this case study, we bring together literatures on identity and culture to examine the boundary work taking place within the United Pentecostal Church International (UPCI), a historically conservative denomination with a fundamentalist orientation toward Christian belief and practice. Our findings demonstrate that boundaries are subject to deviation—and even intentional alteration—at the local level. We introduce the concept of "self‐effacing boundary work" to describe a strategy that deemphasizes exclusionary group practices and beliefs while simultaneously seeking to retain a unique group identity. Organizational leaders and idioculture play key roles in this process.